Monocentric study of IL-5 monoclonal antibody induction therapy for eosinophilic granulomatosis with polyangiitis - Chrong-Reen Wang; Hung-Wen Tsai; Chi-Chang Shieh (Journal of the Formosan Medical Association, 2024)
Objective: Although sporadic case reports have demonstrated successful management of eosinophilic granulomatosis with polyangiitis (EGPA) by anti-IL-5 therapy, larger-scale monocentric studies for the efficacy of mepolizumab (MEP), an IL-5 monoclonal antibody, are still lacking in Taiwan. Methods: Hospitalized EGPA patients aged at least 18 years were enrolled from November 1998 to October 2023, and analyzed for demographic, clinical, laboratory, medication and outcome data, focusing on the efficacy and safety of biologics use, particularly induction therapy with MEP. Results: Twenty-seven EGPA patients aged 10–70 years (43 ± 15) at disease diagnosis were recruited with 21 under combined corticosteroids/cyclophosphamide induction therapy. Seventeen patients received biologics with 13 under MEP therapy. Ten patients aged 19–71 years (48 ± 15) completed 12-month induction therapy with a 100 mg quadri-weekly subcutaneous injection regimen indicated for active or relapse disease. There were reduced BVAS with complete remission in 6 and partial remission in 4 patients, lower CRP levels, decreased eosinophil counts with an inhibition of 92∼96 %, and tapered prednisolone dosages from 5 to 25 (13.0 ± 6.3) to 0–10 (3.3 ± 3.1) mg/day. Only one patient had an adverse event of injection site reactions. Nine patients received the same regimen for annual maintenance therapy. All had a persistent clinical remission. In these patients, 13–56 injections (41 ± 15) were prescribed with a follow-up period of 12∼52 months (38 ± 14). Conclusion: In this retrospective study, induction therapy with a 12-month 100 mg MEP quadri-weekly subcutaneous injection regimen demonstrates the efficacy and safety for active and relapsing EGPA patients.